2008
DOI: 10.1074/jbc.m708145200
|View full text |Cite
|
Sign up to set email alerts
|

ECRG2 Disruption Leads to Centrosome Amplification and Spindle Checkpoint Defects Contributing Chromosome Instability

Abstract: Cancer cells contain an abnormal number of chromosomes (aneuploidy), which is a prevalent form of genetic instability in human cancers. Abnormal amplification of centrosomes and defects of spindle assembly checkpoint are the major causes of chromosome instability in cancer cells. Here we present biochemical evidence to suggest a role of ECRG2, a novel tumor suppressor gene, in maintaining chromosome stability. ECRG2 localized to centrosomes during interphase and kinetochores during mitosis. Further analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…ECRG2 is important for ensuring centrosome duplication and accurate chromosome segregation, and its disruption leads to centrosome amplification and spindle checkpoint defects, contributing chromosome instability. 11 Using yeast two-hybrid system, ECRG2 was found to interact with . By Ad-ECRG2 infection at gradient intensity, nuclear factor (NF)-kB expression was downregulated and matrix metalloproteinase 2 (MMP-2) was reserved in an inactivated form.…”
Section: Discussionmentioning
confidence: 99%
“…ECRG2 is important for ensuring centrosome duplication and accurate chromosome segregation, and its disruption leads to centrosome amplification and spindle checkpoint defects, contributing chromosome instability. 11 Using yeast two-hybrid system, ECRG2 was found to interact with . By Ad-ECRG2 infection at gradient intensity, nuclear factor (NF)-kB expression was downregulated and matrix metalloproteinase 2 (MMP-2) was reserved in an inactivated form.…”
Section: Discussionmentioning
confidence: 99%
“…Reagents-Monoclonal anti-ECRG2 antibody was produced by our laboratory (22,23). Human uPA and uPAR monoclonal antibodies were purchased from American Diagnostica (Greenwich, CT).…”
Section: Methodsmentioning
confidence: 99%
“…All cells were grown in Dulbecco's modified Eagle's medium with 10% fetal bovine serum, 10 mM Hepes, 2 mM L-glutamine, 1 mM minimal essential medium, and sodium pyruvate. We used a doxycycline-inducible expression system to obtain the conditional expression of ECRG2 in HT1080, MDA-MB-231, and MCF-7 cells (ECRG2-Tet-on) as previously described (23). As shown in supplemental Fig.…”
Section: Generation Of Inducible Ecrg2-tet-on Ecrg2-tet-on-3јutr-simentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that ECRG2 is a tumor suppressor gene involved in the regulation of cell proliferation, induction of apoptosis, and inhibition of cancer cell migration, invasion and metastasis (Cui et al 2003;Huang et al 2007). ECRG2 also participates in centrosome amplification in a p53-dependent manner and has a role in maintaining chromosome stability (Cheng et al 2008). Recently, it was found that ECRG2 regulates cell migration/invasion through urokinase-type plasmin activator (uPA)/urokinase-type plasmin activator receptor (uPAR) pathway by directly inhibiting uPA/plasmin activity, and may represent a novel therapeutic target for cancer (Huang et al 2007;Cheng et al 2009Cheng et al , 2010Cui et al 2010).…”
Section: Biological Contextmentioning
confidence: 99%